Structural and functional basis for lipid synergy on the activity of the antibacterial peptide ABC transporter McjD - Mehmood, S; Corradi, V; Choudhury, H; Hussain, R; Becker, P; Axford, D; Zirah, S; Rebuffat, S; Tieleman, D; Robinson, C; Beis, K (American Society for Biochemistry and Molecular Biology, 2017)
The lipid bilayer is a dynamic environment that consists of a mixture of lipids with different properties that regulate the function of membrane proteins; these lipids are either annular, masking the protein hydrophobic surface, or specific lipids, essential for protein function. In this study, using tandem mass spectrometry, we have identified specific lipids associated with the Escherichia coli ABC transporter McjD, which translocates the antibacterial peptide MccJ25. Using non-denaturing mass spectrometry, we show that McjD in complex with MccJ25 survives the gas-phase. Partial delipidation of McjD resulted in reduced ATPase activity and thermostability as shown by Circular Dichroism, both of which could be restored upon addition of defined E. coli lipids. We have resolved a phosphatidylglycerol lipid associated with McjD at 3.4 Å resolution, while molecular dynamic simulations carried out in different lipid environments assessed the binding of specific lipids to McjD. Combined, our data show a synergistic effect of zwitterionic and negatively charged lipids on the activity of McjD; the zwitterionic lipids provide structural stability to McjD whereas the negatively charged lipids are essential for its function.